Comparative Evaluation of Spinal Anesthesia and General Anesthesia in Gynecologic Diagnostic Laparoscopy - Nahid Zirak; Majid Razavi; Leli Hafizi; Farideh Golhasani Keshtan; Nasrin Ahangarian; Nayereh Khadem Ghaebi (Mashhad University of Medical Sciences, 2017)
Introduction: The preferred method in anesthesia of the patients who are candidate for gynecology diagnostic laparoscopic surgeries is general anesthesia (GA) usually, but in patients with any contraindication for GA, Spinal Anesthesia (SA) is used. This study was performed with aim to compare GA with SA technique for gynecology diagnostic laparoscopic surgeries. Methods:  This clinical randomized and prospective study was performed on 30 patients who were candidate for gynecology diagnostic laparoscopic surgeries in 2012-2013. The subjects were divided in two groups of GA & SA (n=15 in each group). Data collection tools were checklist and observation. SPO2، MAP، RR، HR، ETCO2 were recorded preoperative and intraoperative. Nausea, vomiting and shoulder pain were evaluated in recovery, 2, 8 and 24 hours after surgery. Data were analyzed by SPSS software (version 15), and using T-test and Chi-square. P <0.05 was considered significant. Results: The changes of SPO2 and HR at the studied times were not significantly difference between two groups (p=0.141, p=0.531, respectively), and only EtCO2 after Inflation (p=0.015) and RR and EtCO2 during inflation (p=0.004, p=0.013, respectively) were significantly different between two groups. MAP in all the state in the SA group was lower except before inflation. The incidence of shoulder pain at 2,8 and 24 hours after surgery had significant difference between two groups (p=0.009, p=0.035 and p=0.011, respectively); so that it was higher in the SA group. Nausea in the recovery had higher incidence in SA group (p=0.024). Conclusion: The use of SA for diagnostic laparoscopic surgeries in women is safe and reliable and like as any other anesthesia method has benefits and disadvantages.